Determinación histológica de regenerantes de Euchile mariae (Ames) Withner, (Orchidaceae), obtenidos a partir de protocormos cultivados in vitro - Suárez-Quijada, Iris; Sandoval-Zapotilla, Estela; Hernández-Altamirano, Mabel; Chávez-Ávila, Víctor (Lankesteriana: International Journal on Orchidology, 2015)
From the germination of seeds of Euchile mariae in modified MS medium, the formation of pro- tocorms was achieved. Once these reached an average size from 2 to 5 mm long and the formation of his first leaf primordium, they were used like explants to induce a morphogenetic response. Through in vitro culture of top and bottom protocorms sections, were obtained differentiated structures from asexual origin. Their morphology was similar to protocorms obtained from the germination of seeds, in this way we call them protocorm like bodies (PLB’s). Through of the histological analysis of these structures it was possible to reveal that these PLB’s turned out to be somatic embryos. The histochemical tests demonstrate the pres- ence of cellular contents like: proteins, lipids and starch; both in the cells of the embryos as well as in the cells of initial tissues.